Liebstadia (Liebstadia) similis - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Liebstadia (Liebstadia) similis (Michael, 1888) Material – One specimen in Yeşiltepe Area, Akçaabat, Trabzon, N 40° 58′ 24.75′′, E 39° 30′ 25.55′′, alt. = 348 m, 27 May 2018, tree trunk of P. abies; five specimens in Saraycık Forest Processing Area, Taşköprü, 15 July 2018, tree bark and debris of P. nigra . Previous records in Turkey – Erzurum (Ayyildiz 1988), Ankara (Grobler et al. 2004). Global distribution – Holarctic. Ecology – All types of habitats.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 266, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Arachnida; Liebstadia similis; Animalia; Liebstadiidae; Biodiversity; Sarcoptiformes; Liebstadia; Taxonomy; 2. Zero hunger; 15. Life on land